Single Trial Visual Evoked Potential Estimation using Partial Least Squares Based Approach - YANTI HUTAPEA, DUMA KRISTINA (2018)
The nature of visual evoked potential (VEP) signals which is very low in power makes it difficult to be obtained except by gathering a series of time-locked electroencephalogram (EEG) epochs and performing ensemble averaging on these samples to improve the power. In the clinical use, the averaging of these VEP signals is used to conduct the measurement of the optical pathway or disease assessment.